Exploring Approaches to Italian Early Medieval Archaeology in Post-communist Europe - Vollono, Giulia (Ex Novo: Journal of Archaeology, 2016)
The fall of the Berlin Wall and, subsequently, of communism in Europe had profound consequences for the social and political environment of many European countries, including Italy. In this paper I discuss the impact that these, now historical, events and the new socio-political arena that emerged in their aftermath had upon Italian Early Medieval Archaeology from two interconnected perspectives. On the one hand I consider the history of a discipline that, although strongly characterised by a Marxist approach at its birth, appears not to have been subject to significant changes in its theoretical outlook as a consequence. On the other, through a consideration of the changing character of major exhibitions on the Lombard period, I explore the role that archaeology has played in the construction of a trans-national European narrative in a post-communist Europe while maintaining a central role in the negotiation of local identities. The ultimate aim of this paper is to re-evaluate the latest developments in Italian archaeology from a fresh perspective, considering the impact that major contemporary events can have on our perception, interpretation and narration of the past.